OMBUDSMAN STRATEGY OF REPUBLIC OF INDONESIA IN EAST JAVA REPRESENTATIVE REGARDING PUBLIC SERVICE SUPERVISION - Marianus Yofan Kader; Willy Tri Hardianto (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstrack: Establishing Ombudsman institution was aimed to aid in creating and developing favorablecondition in implementation of Corruption and Nepotism (KKN) through people’s participation. Goodgovernmental and state implementation would only achieved by improving the quality of state apparatusin its governments, also maintain good government principles. The task of ombudsman is to investigatereports under the presumption of maladministration in its public service’s supervision. Study method usedin this paper was qualitative method. Data collection technique was using observation, interview anddocumentation to support data verification. Data analysis methods used were data reduction, datapresentation and data verification. Study results showed that Ombudsman strategy of Republic ofIndonesia in East Java Representative has obedience strategy toward public service standard as one ofthe target to achieve National Medium Term Development Plan (RPJMN). Its supporting factors wouldbe commitment from public service institution in coordination with Ombudsman and various Ombudsmannetwork such as Ombudsman friends in regional area, while its impeding factors would be the limitednumber of employees. To execute the work and function of Ombudsman, sufficient employees should bemet in order to avoid lack of employees in completing the works and function of Ombudsman.Keywords: Ombudsman Strategy; Public ServiceAbstrak: Pembentukan lembaga Ombudsman bertujuan untuk membantu menciptakan danmengembangkan kondisi yang kondusif dalam melaksanakan pemberantasan Korupsi, Kolusi, danNepotisme (KKN) melalui peran serta masyarakat. Penyelenggaraan negara dan pemerintahan yang baikhanya dapat tercapai dengan peningkatan kualitas aparatur penyelenggara negara dan pemerintahan, jugapenegakan asas-asas pemerintahan umum yang baik.Tugas Ombudsman adalah memeriksa laporan atasdugaan maladministrasi dalam penyelenggaraan pelayanan publik.Tujuan penelitian ini adalah untukmengetahui strategi Ombudsman dalam pengawasan pelayanan publik.Metode penelitian yang digunakanadalah kualitatit.Teknik pengumpulan data dalam penelitian ini adalah pengamatan (observasi),wawancara (interview) dan dokumentasi untuk mendukung keabsahaan data.Metode analisis data yangdigunakan adalah reduksi data, penyajian data dan verification. Hasil penelitian membuktikan bahwastrategi Ombudsman Republik Indonesia perwakilan Provinsi Jawa Timur memiliki strategi kepatuhanterhadap standar pelayanan publik sebagai salahsatu target pencapaian Rencana Pembangunan JangkaMenengah Nasional (RPJMN). Adapun faktor pendukung yaitu komitmen dari instansi penyelenggarapelayanan publik berkoordinasi dengan Ombudsman dan jaringan Ombudsman yang banyak sepertisahabat-sahabat Ombudsman di daerah, sedangkan faktor penghambat adalah jumlah pegawai yangterbatas.Untuk menjalankan tugas dan fungsi Ombudsman harus menyediaakan pegawai yang cukup agartidak terjadi persoalan seperti kurangnya pegawai dalam menyelesaikan tugas dan fungsi Ombudsman.Kata kunci: Strategi Ombudsman; Pelayanan Publik